2013
DOI: 10.1016/j.celrep.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Characterization of Factors Enriched at Nascent DNA Molecules

Abstract: DNA replication is facilitated by multiple factors that concentrate in the vicinity of replication forks. Here, we developed an approach that combines the isolation of proteins on nascent DNA chains with mass spectrometry (iPOND-MS), allowing a comprehensive proteomic characterization of the human replisome and replisome-associated factors. In addition to known replisome components, we provide a broad list of proteins that reside in the vicinity of the replisome, some of which were not previously associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
101
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 62 publications
(75 reference statements)
13
101
1
Order By: Relevance
“…In vitro studies demonstrated that hCtf4 stimulated reactions catalyzed by Pol α and Pol e and weakly interacted with these Pols (19). Furthermore, recent studies on the identification of replisome proteins revealed the association of hCtf4 with nascent DNA chains (26).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies demonstrated that hCtf4 stimulated reactions catalyzed by Pol α and Pol e and weakly interacted with these Pols (19). Furthermore, recent studies on the identification of replisome proteins revealed the association of hCtf4 with nascent DNA chains (26).…”
Section: Discussionmentioning
confidence: 99%
“…By labeling cells with EdU at 3.5 h after infection, we took advantage of the dramatic decrease in EdU incorporation into nuclear DNA to preferentially label viral DNA. With some modifications that further enriched viral DNA, the protocol closely followed that previously used (63)(64)(65). We chose iPOND over the alternative AniPOND procedure (83) because formaldehyde cross-linking allows stringent washing of the beads with SDS.…”
Section: Discussionmentioning
confidence: 99%
“…To address gaps in knowledge of the VACV DNA replication and transcription machinery, we adapted recently developed click chemistry methods for visualizing newly synthesized chromosomal DNA (61,62) and for isolating and identifying protein components of nuclear eukaryotic (63)(64)(65) and herpesvirus (66,67) replisomes. The method is based on the in vivo incorporation of ethynyl deoxynucleoside analogs, such as 5-ethynyl-2=-deoxyuridine (EdU), into replicating DNA.…”
mentioning
confidence: 99%
“…To identify potential nucleases and helicases required for processing replication forks after 2 hours exposure to HU, we used siRNAs to knock down enzymes known to act on collapsed forks plus those identified at unperturbed and stalled replication forks through iPOND analysis [36][37][38]. Knockdown of EXO1, BLM, and CtIP reduced phospho-CHK1 levels in response to HU whereas MRE11 knockdown did not ( Figure 3A and Supplementary Figure 4A).…”
Section: Ddk Likely Promotes Fork Processing By Regulating the Activimentioning
confidence: 99%